Wynagrodzenia dyrektorskie ze spółek maltańskich – unikanie czy uchylanie się od opodatkowania? - Nawrot, Rafał Aleksander (Kwartalnik Prawa Podatkowego, 2015)
This article analyses the issue of tax and legal qualification of directors’ remunerations received by Polish tax residents from Maltese companies. This mechanism became quite popular in recent years as a way of tax avoidance, what comes out of the high number of individual tax rulings granted by Ministry of Finance in this respect. The analysis of the Maltese law and Polish-Maltese double taxation treaty leads to conclusion that directors’ remunerations in strict sense paid out by Maltese companies to Polish tax residents are taxed in Malta with no regard to the fact if the directors’ duties are carried out in Malta or outside its territory. At the same time these remunerations are tax exempted in Poland in accordance with regulations of Polish-Maltese double taxation treaty. In contradiction to what was mentioned above remunerations of Maltese companies’ directors who are Polish tax residents paid out on a different legal basis than management and supervision on these companies are tax exempted in Malta and taxed in Poland on general terms. As a consequence of lack of possibility of legal double non-taxation of directors’ remunerations paid out from Maltese companies (taxation appears in Poland or in Malta) director’s appointment in such companies does not constitute a way of international tax avoidance. This leads to a thesis of significant inconsistencies between tax returns of Polish taxpayers receiving these remunerations and tax returns of Maltese companies which pay out these charges, i.e. Polish taxpayers declare in their annual tax returns the receipt of directors’ remunerations in strict sense (in the meaning of art. 16 of Polish-Maltese double taxation treaty) and simultaneously the Maltese companies declare this amounts as directors’ salaries based on different legal titles (in the meaning of art. 15 of Polish-Maltese double taxation treaty). Only in the above way a double non-taxation of Maltese company director’s remuneration can be provided, what constitutes tax evasion. A proof of this thesis is the major scientific aim of this publication, filling in a certain gap in present Polish publications.